Implikasi Hukum Pemisahan Produk Simpanan dan Investasi pada Perbankan Syariah Pasca Peraturan Otoritas Jasa Keuangan Nomor 4 Tahun 2026 - Gatot Teguh Arifyanto (Medan Resource Center, 2026)
This study analyzes the legal framework governing the separation of deposit and investment products under Financial Services Authority Regulation Number 4 of 2026 concerning the Administration of Investment Products in Islamic Banking, its implications for Islamic banking contracts, investor-customer protection, and implementation challenges. The regulation was enacted pursuant to Law Number 4 of 2023 on the Development and Strengthening of the Financial Sector to establish a clear legal distinction between deposit and investment products in Islamic banking. This research employs a normative juridical method using statutory and conceptual approaches, with primary, secondary, and tertiary legal materials analyzed through qualitative deductive reasoning. The findings reveal that the regulation fills a significant regulatory gap by clarifying product classification, requiring separate record-keeping, and strengthening fiduciary duties. It also requires the restructuring of wadī'ah and muḍārabah contracts, excludes investor-customers from the Indonesia Deposit Insurance Corporation guarantee scheme, and poses challenges related to accounting, risk management, and institutional readiness. The study concludes that strengthening implementing regulations, refining suitability assessment mechanisms, updating National Sharia Council fatwas, and enhancing risk management are essential to ensure legal certainty and equitable protection for investor-customers.